A Nice, Quick, and Easy Polynomial System

preview_player
Показать описание
If you need to post a picture of your solution or idea:
#ChallengingMathProblems #PolynomialEquations #PolynomialSystems
via @YouTube @Apple @Desmos @NotabilityApp
@googledocs @canva

PLAYLISTS 🎵 :

Рекомендации по теме
Комментарии
Автор

Let t=x+y+z, then the given expressions can be written as follows:

x^2-x+t-15=0
y^2-y+t-15=0
z^2-z+t-15=0

Therefore, x, y & z are either of the two solutions of k^2-k+t-15=0.

k=(1±√(61-4t))/2

Let α=(1+√(61-4t))/2 & β=(1-√(61-4t))/2, then

t=x+y+z=3α, 3β, 2α+β or 2β+α

t=3α⇒t=9, -15⇒t=9(∵t>0)⇒x=y=z=3
t=3β⇒t=9, -15⇒t=-15(∵t=9 isn't suitable)⇒x=y=z=-5
isn't suitable)⇒(x, y, z)={1-√14, √14, √14}
isn't suitable)⇒(x, y, z)={1+√14, -√14, -√14}

vacuumcarexpo
Автор

When the conditions are the same for all equations, it means x=y=z🙂
It also means the equality of part to part.
Of course, for the integer roots

morteza
Автор

The smell of new Sybermath in the morning is so refreshing!

WEAVER
Автор

Since the three eqns have the same sum, we can conclude that the three variables are equal to each other

x + y + z²= 15
=> x + x + x²= 15
=> x² + 2x - 15= 0

Using the Quadratic Formula
[-2 ± Sqrt(2²-4(1)(-15))]/2
=> -5 and 3

Thus the answer(s) is/are:
(3, 3, 3) and (-5, -5, -5)

threstytorres
Автор

I found a geometric method to solve quadratic equations.
ax²+bx+c=0

α=arcsin(2c/ar²)/2
X1=R(sin(α))
X2=R(cos(α))
But it is long.

morteza
Автор

what about case 3 when (z+y-1)=0 and (y+x-1)=0

אסףחברוני
Автор

i assumed x = y = z and found the two symmetric solutions and then assumed x = z, combined the two resulting equations, and ended up with a quartic that factored as
(x - 3)(x + 5)(x^2 - 14) = 0

wasn't sure how to demonstrate that there were no solutions with x ≠ y ≠ z

coreyyanofsky
Автор

What i did was:
x+y+z²=15 and subtract another equation
-y-z-x²=-15
They add up to
x-z+z²-x²=0
Then add -z²+x² to both sides
And get
x-z = x²-z² which happens to be:
x-z = (x-z)(x+z) divide both side by x-z
x+z = 1
Subtitute it in the 2nd equation where we have that expression
1 + y² = 15
y²=14
y=+-sqrt14
And then we can repeat the first step
This time choosing different equations
And we get
x+y=1 and we know y
x+sqrt14=1
x=1-sqrt14
Put the new x in x+z=1
And get that z = sqrt 14 aswell
x, y=z ---> 1-sqrt14, sqrt 14, sqrt 14.
Or if we used the negative result in the first place we wouldve gotten the second variation of this

Awesome-ctvr
Автор

x =3 y =3 and z =3
x+ z + y^2 = x+ y +z^2 since both = 15
z+ y^2 = y + z^2
z-y = z^2 - y^2
z-y = (z+y)(z-y)
z+y=1 or z-y=0
z-y doesn't = 1, but the value areas 0 then z and y are equal
hence
y+ z +x^2 = x+y+ z^2
z+x^2 = x + z^2
z-x = z^2-x^2
z-x= (z-x) (z+x)
z+x = 1 or z-x =0
here again z-x = 0 hence z and x are equal
hence x= z = y
hence
using x+z + y^2 =15 yields
y+ y + y^2 =15
2y + y^2 =15
y^2 + 2y -15 =0
(y-3)(y+5) = 0
y= 3 and y =-5
y =3 x =3 and z =3 answer

devondevon
Автор

Shouldn't you also cover case 3, where x+y=1 and y+z=1, if only to show why this can't produce a solution?

ZipplyZane
Автор

Didn't you miss case 3 where y+z=1 AND x+y=1 ?

valdemie
Автор

My comment was blocked for some reason.

I'll rewrite it.

Let t=x+y+z, then the given expressions can be written as follows:

x^2-x+t-15=0
y^2-y+t-15=0
z^2-z+t-15=0

Therefore, x, y & z are either of the two solutions of k^2-k+t-15=0.

k=(1±√(61-4t))/2

Let α=(1+√(61-4t))/2 & β=(1-√(61-4t))/2, then

t=x+y+z=3α, 3β, 2α+β or 2β+α

t=3α⇒t=9, -15⇒t=9(∵t>0)⇒x=y=z=3
t=3β⇒t=9, -15⇒t=-15(∵t=9 isn't suitable)⇒x=y=z=-5
isn't suitable)⇒(x, y, z)={1-√14, √14, √14}
isn't suitable)⇒(x, y, z)={1+√14, -√14, -√14}

vacuumcarexpo
Автор

Since the three equations are symmetric this we can say that x=y=z
Now by substituting all variables to x in eqn 1 we get x+x+x²=15
So 2x + x ² = 15
Thus x(2+x) =15
There are two possible values for this equation which is x=3 or x=-5

RahulKumar-ckhr
Автор

x=3;y=3;z=3 also satisfy the equations.

gopalsamykannan
Автор

x = 3, y = 3, z = 3
x = -5, y = -5, z = -5

rakenzarnsworld
Автор

By just observation, one can give one of the possible answer and i.e.x=y=z=3

shrikrishnagokhale
Автор

Io ho trovato le soluzioni banali x=y=z che danno (3, 3, 3), (-5, -5, -5) poi forse ce ne sono delle altre, boh

giuseppemalaguti
Автор

I only looked at the thumbnail, but it's x=3 y=3 z=3 next!

gressorialNanites
Автор

It is too bad the terms nice, quick and easy must appear in the thumbnail to induce viewers to click.

One can make up as many of these type of equations as one wants where it all works out “nicely” 😊

MyOneFiftiethOfADollar
Автор

you make it complicated, when you find out z=y or z+y=1. For example, we use z=y as (1) and replace it in (2) and (3), we can easily solve this, similarly for z+y=1.

ngdluu